Enhanced removal of diclofenac via coupling Pd catalytic and microbial processes in a H2-based membrane biofilm reactor: Performance, mechanism and biofilm microbial ecology. (November 2022) - Liu, Yanfen; Xi, Yanni; Xie, Tanghuan; Liu, Huinian; Su, Zhu; Huang, Yicai; Xu, Weihua; Wang, Dongbo; Zhang, Chang; Li, Xin
Abstract: Diclofenac (DCF) is a most widely used anti-inflammatory drug, which has attracted worldwide attention given its low biodegradability and ecological damage, especially toxic effects on mammals including humans. In this study, a H2 -based membrane biofilm reactor (H2 -MBfR) was constructed with well-dispersed Pd nanoparticles generated in situ. The Pd-MBfR was applied for catalytic reductive dechlorination of DCF. In batch tests, DCF concentration had significantly effect on the rate and extent DCF removal, and NO3 − had negative impact on DCF reductive dechlorination. Over 67% removal of 0.5 mg/L DCF and 99% removal of 10 mg/L NO3 − -N were achieved in 90 min, and the highest removal of 97% was obtained at 0.5 mg/L DCF in the absence of NO3 − . Over 78 days of continuous operation, the highest steady-state removal flux of DCF was 0.0097 g/m 2 /d. LC-MS analysis indicated that the major product was 2-anilinephenylacetic acid (APA). Dechlorination was the main removal process of DCF mainly owing to the catalytic reduction by PdNPs, microbial reduction, and the synergistic reduction of microbial and PdNPs catalysis using direct delivery of H2 . Moreover, DCF reductive Dechlorination shifted the microbial community in the biofilms and Sporomusa was responsible for DCF degradation. In summary, this work expands a remarkable feasibility of sustainable catalytic removal of DCF. Graphical abstract: Image 1 Highlights: The Pd-MBfR was successfully developed for long-term removal of DCF. The Pd-MBfR accomplished the simultaneous removal of diclofenac and nitrate. The synergistic reaction of Pd and DCF-degrading bacteria led to dechlorinating DCF. High Sporomusa was one of the contributors for efficient DCF dechlorination.